Academic Performance And Level Of Life Support Skills Among Working Students In Naval State University, Naval, Biliran - Tancinco, Noel P.; Garcia, Carlos B. (Advances in Social Sciences Research Journal, 2020)
This study sought to determine the academic performance and life support skills among working students enrolled in Naval State University during School Year 2016-2017. The respondents of the study were college working students enrolled in six colleges with different courses offered, the parents, teachers and employers were included. The descriptive-correlational research design was employed using a questionnaire to gather information on the respondents. Frequency, percentage and mean were used to describe the respondents’ profile, t-test was used to describe the difference between the academic performance and life support skills, and chi-square test was used to describe the relationship of the variables. The findings of the study revealed that the biggest number of working students were in the College of Industrial, Information and Communications Technology and employed as house helpers, working with an average of 4-5 hours with a very low monthly salary, and a moderately favorable attitude towards work. Moreover, the attitude towards schooling of the working students was moderately favorable, effectiveness of the teachers moderately effective and most of them were affiliated with Youth for Christ and have low attitude towards peers. The heads of the family of the working students were only high school graduates mostly with a low monthly family income. As to the number of siblings, most of them had 3-4 siblings with their own house. Majority of the parents were skilled workers and most of the working student-respondents were living with their parents and obtained with a very good academic performance. For life support skills, most of the teacher-respondents, parents, employers and the working students perceived cognitive, socialization and affective oriented profile as satisfactory. The cognitive life support skills were significantly related to salary, the socialization-related life support skills were significantly related to nature of work, and the affective-oriented life support skills were significantly related to nature of the work and salary. The cognitive life support skills and attitude towards schooling were significantly related to academic performance, socialization-related life support skills were significantly related to academic performance, attitude towards schooling and effectiveness of teachers. Peer profile was not significantly related to cognitive socialization and affective oriented life support skills. The cognitive life support skills were significantly related to the nature of parents’ work and number of siblings. Socialization-related life support skills were significantly related to highest educational attainment of head of the family. Likewise, affective-oriented life support skills were not significantly related to family profile. Thus, the study found out that the best predictors of the level of life support skills among working students through multiple regression analysis of the variables were nature of work, attitude towards schooling and academic performance. The study recommends special attention should be paid to working students by providing them a mechanism to increase and develop their life support skills.